PENGARUH VOLUME SAMPEL DARAH DENGAN ANTIKOAGULAN K2EDTA TERHADAP KADAR HEMATOKRIT - indah sari (Masker Medika, 2023)
Introduction: Pre-analytical stage errors contributed the most to laboratory errors (46-77.1%). Some things that include pre-analytical errors include hemolysis (53.2%), insufficient specimen volume (7.5%), unreadable handwriting (7.2%), wrong specimen, specimen has clot, vacuum error container or type of anticoagulant, specimen volume ratio and inappropriate anticoagulant. Research: aims to determine the effect of blood sample volume with K2EDTA anticoagulant on Hematocrit Levels. Methods: manual method and automatic method. Data analysis used normality test, data transformation test, Wilcoxon test using SPSS. The sampling technique used Nonprobability in the form of Purprosive sampling. This research was conducted at the Muhammadiyah IKesT Hematology Laboratory and RS. Bunda Palembang in February – March 2023. The study used EDTA blood samples from grade 2 and 3 female students DIV IKesT Muhammadiyah Palembang Medical Laboratory. Results: the average hematocrit examination with 3CC EDTA blood volume was 54.1% and 1CC EDTA blood was 42.3%. The conclusion of the study is that there is an effect of blood sample volume with K2EDTA anticoagulant on hematocrit levels. Discussion: there is an effect of blood sample volume with K2EDTA anticoagulant on hematocrit levels.